2012
DOI: 10.1029/2012gl051319
|View full text |Cite
|
Sign up to set email alerts
|

The density and porosity of lunar rocks

Abstract: [1] Accurate lunar rock densities are necessary for constructing gravity models of the Moon's crust and lithosphere. Most Apollo-era density measurements have errors of 2-5% or more and few include porosity measurements. We report new density and porosity measurements using the bead method and helium pycnometry for 6 Apollo samples and 7 lunar meteorites, with typical grain density uncertainties of 10-30 kg m À3 (0.3-0.9%) and porosity uncertainties of 1-3%. Comparison between igneous grain densities and norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
152
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 158 publications
(163 citation statements)
references
References 36 publications
10
152
0
1
Order By: Relevance
“…Both of these values are in keeping with the measured porosities of lunar samples (Kiefer et al, 2012). However, subsequent GRAIL analyses have shown that the best-fit density and porosity is a function of wavelength, consistent with a density that increases with depth, with an average farside density gradient of 35 kg/m 3 /km .…”
Section: Crustal Thickness Modelingsupporting
confidence: 52%
See 3 more Smart Citations
“…Both of these values are in keeping with the measured porosities of lunar samples (Kiefer et al, 2012). However, subsequent GRAIL analyses have shown that the best-fit density and porosity is a function of wavelength, consistent with a density that increases with depth, with an average farside density gradient of 35 kg/m 3 /km .…”
Section: Crustal Thickness Modelingsupporting
confidence: 52%
“…This interpretation is supported by the fact that some of the negative gravity gradients are aligned with smooth non-mare material within the depressions adjacent to the Outer Rook, though in other places the negative gravity gradient ring occurs in rough high-standing material. However, this interpretation is at odds with the corrugated and fractured appearance of the Orientale melt in the Maunder formation that is suggestive of a high porosity (Head, 1974), and the measured high porosity of lunar impact melt breccias (Kiefer et al, 2012). Melted mantle material that has been predicted to splash out over the surface during the impact could provide a greater density contrast ), but has not been identified in remote sensing data.…”
Section: Gravity Gradientsmentioning
confidence: 38%
See 2 more Smart Citations
“…However, the samples obtained from the Apollo missions, as well as lunar meteorites, show that the lunar crust is compositionally heterogeneous, with major rock types including anorthosite, norite, troctolite, and sometimes gabbro (Dymek et al, 1976;Papike et al, 1998;Warren, 1993;Wieczorek et al, 2006). The samples vary widely in both porosity and density (Kiefer et al, 2012a), and the distribution of equivalent rocks in the crust is not constrained. Similar variations in density arising from composition and porosity would be the likely explanation for both the large-scale and small-scale density variations observed in the GRAIL data.…”
Section: Introductionmentioning
confidence: 99%